2010
DOI: 10.1007/s11999-010-1535-x
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Insufficiency Fractures Associated with Prolonged Bisphosphonate Therapy

Abstract: Background Emerging evidence has linked the long-term use of bisphosphonates with femoral insufficiency fractures. It has been suggested that the prolonged effect on bone remodeling leads to the accumulation of microfractures and weakening of bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 55 publications
5
63
0
9
Order By: Relevance
“…Only nine fractures were in men, but gender was not identified in three large case series. (100,107,108) The majority (160 of 189) occurred after oral alendronate monotherapy: 12 patients were treated with oral risedronate (of these, 1 was followed by oral alendronate, whereas 2 were treated previously with alendronate and another was treated previously with pamidronate), 4 with a combination of intravenous pamidronate followed by intravenous zoledronic acid (myeloma), 4 with either oral or intravenous pamidronate (osteoporosis), 2 with intravenous zoledronic acid (renal cell carcinoma and osteoporosis), 2 with oral alendronate followed by oral ibandronate, and 102 with an unspecified oral BP.…”
Section: Atypical Subtrochanteric and Femoral Shaft Fractures: Clinicmentioning
confidence: 99%
“…Only nine fractures were in men, but gender was not identified in three large case series. (100,107,108) The majority (160 of 189) occurred after oral alendronate monotherapy: 12 patients were treated with oral risedronate (of these, 1 was followed by oral alendronate, whereas 2 were treated previously with alendronate and another was treated previously with pamidronate), 4 with a combination of intravenous pamidronate followed by intravenous zoledronic acid (myeloma), 4 with either oral or intravenous pamidronate (osteoporosis), 2 with intravenous zoledronic acid (renal cell carcinoma and osteoporosis), 2 with oral alendronate followed by oral ibandronate, and 102 with an unspecified oral BP.…”
Section: Atypical Subtrochanteric and Femoral Shaft Fractures: Clinicmentioning
confidence: 99%
“…Early case reports found that atypical fractures occurred in younger people than ordinary fractures, often occurred bilaterally, with prodromal pain, and were not preceded by obvious trauma. (7,8) The atypical fracture appearance was rarely observed prior to the introduction of bisphosphonates. (9) A task force of the American Society for Bone and Mineral Research called for additional epidemiological data to establish the true incidence of these fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Nesta vertente, os nossos resultados são apoiados pela literatura com resultados de odds ratio de 9,46 em doentes com tratamento superior a três anos (Erviti et al) 15 ; 66,9 em doentes com uma mediana de duração de tratamento no grupo entre os 5-9 anos (Meier et al) 5 ; e 1000 em doentes com tratamento médio de 7,1 anos (Isaacs et al), 6 resultados estes também estatisticamente significativos e com intervalos de confiança de 95%.…”
Section: Discussionunclassified
“…6 O mesmo autor defende, se não a suspensão dos bifosfonatos ao fim de cinco anos, pelo menos a pesquisa activa de sintomas prodrómicos e monitorização radiográfica. No caso da nossa população em estudo estavam apenas descritos sintomas prodrómicos com uma duração de seis meses no caso da doente com fractura atípica bilateral simultânea.…”
Section: Discussionunclassified
See 1 more Smart Citation